Application of impedance spectroscopy to evaluate the effect of different setting accelerators on the developed microstructures of calcium phosphate cements - Romeo, H. E.; Bueno, P. R. [UNESP]; Fanovich, M. A. (Springer, 2009)
The main goal of the present study was to evaluate the effect of different setting accelerator agents on the developed microstructures of calcium phosphate cements (CPCs) by employing the impedance spectroscopy (IS) technique. Six compositions of CPCs were prepared from mixtures of commercial dicalcium phosphate anhydrous (DCPA) and synthesized tetracalcium phosphate (TTCP) as the solid phases. Two TTCP/DCPA molar ratios (1/1 and 1/2) and three liquid phases (aqueous solutions of Na(2)HPO(4), tartaric acid (TA) and oxalic acid (OA), 5% volume fraction) were employed. Initial (I) and final (F) setting times of the cement pastes were determined with Gillmore needles (ASTM standard C266-99). The hardened samples were characterized by X-ray powder diffraction (XRD), Fourier transformed infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and apparent density measurements. The IS technique was employed as a non-destructive tool to obtain information related to porosity, tortuosity and homogeneity of the cement microstructures. The formulation prepared from a TTCP/DCPA equimolar mixture and OA as the liquid phase presented the shortest I and F (12 and 20 min, respectively) in comparison to the other studied systems. XRD analyses revealed the formation of low-crystallinity hydroxyapatite (HA) (as the main phase) as well as the presence of little amounts of unreacted DCPA and TTCP after 24 h hardening in 100% relative humidity. This was related to the proposed mechanisms of dissolution of the reactants. The bands observed by FTIR allowed identifying the presence of calcium tartrate and calcium oxalate in the samples prepared from TA and OA, in addition to the characteristic bands of HA. High degree of entanglement of the formed crystals was observed by SEM in samples containing OA. SEM images were also correlated to the apparent densities of the hardened cements. Changes in porosity, tortuosity and microstructural homogeneity were determined in all samples, from IS results, when the TTCP/DCPA ratio was changed from 1/1 to 1/2. The cement formulated from an equimolar mixture of TTCP/DCPA and OA as the liquid phase presented setting times, degree of conversion to low-crystallinity HA and microstructural features suitable to be used as potential bone cement in clinical applications. The IS technique was shown to be a very sensitive and non-destructive tool to relate the paste composition to the developed microstructures. This approach could be very useful to develop calcium phosphate bone cements for specific clinical demands.